CAUSES OF EARLY AGE MARRIAGE IN SIGI DISTRICT, SULAWESI CENTRAL - Hadriani Hadriani; Hadina Hadina; Arie Maeneny; Suci Kur'ani Kanitaon (Media Kebidanan, 2020)
Marriage is something that is expected in human life because through a marriage a family is formed that produces offspring. In Indonesia, early marriage is considered to violate the law of marriage and there are still many early marriages taking place, especially in rural areas, thus creating controversy. This study aims to determine the factors that cause early marriage in the district of Marawola, Sigi, Central Sulawesi. The research method uses qualitative methods with the type of case study research. Research informants were women who were married early, namely age <20 years, female parents who were married early, the Head of the Office of Religious Affairs (KUA) and Community Leaders in Marawola Subdistrict, Sigi Regency, Central Sulawesi using snowball sampling techniques. Results of the Factors Causing Early Childhood Marriage in Women in Marawola Subdistrict, Sigi Regency, Central Sulawesi are social factors, self-will, informant's education and parents of informants and parental care patterns. The conclusion is that the factors causing early marriage in women in Marawola Subdistrict, Sigi Regency, Central Sulawesi are social environment factors, their own desires, knowledge, parenting, economic, family culture and religion. Suggestions in this study are expected for young women, health workers, parents, the community and researchers to participate in efforts to prevent early marriage, especially for women.Keywords : Early marriage, women